2023
DOI: 10.1186/s12890-023-02306-w
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles and bioinformatics analysis in lung samples from ovalbumin-induced asthmatic mice

Abstract: Background Asthma is characterized by chronic inflammation and airway remodeling. However, limited study is conducted on the gene expression profiles of ovalbumin (OVA) induced asthma in mice. Here, we explored the gene expression profiles in lung tissues from mice with OVA-induced asthma using microarray and bioinformatics analysis. Methods For establishment of OVA-induced asthma model, mice first received intraperitoneal sensitization with OVA on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg 7,17–19 . However, the effects of various doses within this range have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg 7,17–19 . However, the effects of various doses within this range have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg. 7 , 17 , 18 , 19 However, the effects of various doses within this range have not been thoroughly investigated. In 1999, Sakai et al 20 demonstrated the impact of sensitive OVA doses (0, 10, 100, and 1000 μg) on AHR; their study suggested that sensitization with a dose of 10 μg may be more effective than with a dose of 100 μg but almost completely inhibited at a dose of 1000 μg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations